Formulasi Dan Uji Aktivitas Antipiretik Plester Hidrogel Ekstrak Etanol Daun Sirsak (Annona muricata L.) - Murina, Debi Meilani (Journal of Health and Medical Science, 2022)
Fever is a condition in which the body temperature is more than 37 °C, fever can also be an early clinical manifestation of a particular infection. A person is said to have a fever when the body temperature is above normal. Soursop plant (Annona muricata L.) is one of the plants that have antipyretic effects because it contains secondary metabolite compounds, namely flavonoids that can reduce fever. The objective of the research was to simulate the Formulation and Antipyretic Activity Test of Hydrogel Plasters of Soursop Leaf Ethanol Extract (Annona muricata L.) Soursop leaf ethanol extract is made by the maceration method, formulated as a hydrogel plaster with different concentrations of 5 g, 7.5 g, and 10 g. and then testing is carried out which includes organoleptic tests, pH tests, viscosity tests, homogeneity tests, and temperature reduction tests on mice. The test data obtained was then analyzed using SPSS (Statistical Package for The Social Sciences) and the Anova test was then continued using the Tukey test. The results showed that the three hydrogel preparations had the same organoleptic results, namely semi-solid shape, distinctive smell and dark green brownish. The pH of the hydrogel includes 5 - 6.2, viscosity 89510 - 106530 cP and homogeneous preparations. The results of the test of the decline in body temperature of mice test animals showed that the most effective formula was hydrogel plaster with a composition of 10 g of extract in 30 g of preparations can lower the body temperature of mice in the fastest time, which is 60 minutes.